Gustav Stresemann : the crossover artist - Pohl, Karl Heinrich, 1943- (Studies in German history, 2019)
"As a foreign minister and chancellor of Weimar Germany, Gustav Stresemann is a familiar figure for students of German history - one who, for many, embodied the best qualities of German interwar liberalism. However, a more nuanced and ambivalent picture emerges in this award-winning biography, which draws on extensive research and new archival material to enrich our understanding of Stresmann's public image and political career. It memorably explores the personality of a brilliant but flawed politician who endured class anxiety and social marginalization, and who died on the eve of Germany's descent into economic and political upheaval."--Provided by publisher.